The Impact of Information Content and Entertainment Content on Customer Engagement and Customer Loyalty: A Study on Scarlett's Customer Base - Ali Sandi, Heanjelika; Tema Atmaja, Ferry (Journal of Entrepreneurship and Business, 2024)
Purpose: The primary objective of this study is to comprehend the influence of two distinct types of content on customer engagement and loyalty, with a specific emphasis on the Instagram platform. Additionally, the research seeks to investigate how the content on Instagram can impact consumer engagement behaviors and loyalty toward Scarlett products. Method: Data for this study were collected through a survey link. The survey was distributed to 223 participants, with 176 respondents actively participating. However, only 147 questionnaires met the established criteria for inclusion, as the remainder still needed to satisfy the stipulated requirements. The data analysis was conducted utilizing the SmartPLS4 software. Result: The findings of this study indicate that both informational and entertainment content significantly influence customer engagement and loyalty. However, it is noteworthy that customer engagement, as identified in this research, has little impact on customer loyalty. Consequently, it is imperative to create and reinforce all facets of informational and entertainment-based content. Doing so will stimulate more active engagement from social media followers, directly influencing customer loyalty.